2019
DOI: 10.3390/f10050406
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with High-Dose Gamma Irradiation on Seeds Enhances the Tolerance of Sweet Osmanthus Seedlings to Salinity Stress

Abstract: The landscape application of sweet osmanthus (Osmanthus fragrans) with flower fragrance and high ornamental value is severely limited by salinity stress. Gamma irradiation applied to seeds enhanced their tolerance to salinity stress as reported in other plants. In this study, O. fragrans ‘Huangchuang Jingui’ seeds were pretreated with different doses of gamma irradiation, and tolerance of the seedlings germinated from the irradiated seeds to salinity stress and the changes of reactive oxygen species (ROS) prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Results illustrated in Table 9 and Fig. 4 related to POX isozymes are in agreement with Geng et al (2019) who study the effect of higher doses of gamma radiation on seeds of sweet osmanthus before germination. On the contrary, band number 2 appeared with different intensities and densities in all treatments as compared to control which shows the varying enzyme status under stress conditions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results illustrated in Table 9 and Fig. 4 related to POX isozymes are in agreement with Geng et al (2019) who study the effect of higher doses of gamma radiation on seeds of sweet osmanthus before germination. On the contrary, band number 2 appeared with different intensities and densities in all treatments as compared to control which shows the varying enzyme status under stress conditions.…”
Section: Discussionsupporting
confidence: 89%
“…Successive exposure of plants for different stresses factors in the environment such as salinity, drought, heat, and high light leading to increased accumulation of reactive oxygen species (ROS) (Carvalho 2008;Suzuki et al 2012). Subsequently, ROS affected on most plant cell functions by damaging of protein, DNA, and lipids (Kai et al 2012;Geng et al 2019). Generally, plant cells use two mechanisms to detoxify ROS, enzymatic antioxidants such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POX), ascorbate peroxidase (APX), glutathione reductase (GR), and dehydroascorbate reductase (DHAR) and non-enzymatic low molecular weight antioxidants such as ascorbate, α-tocopherol, carotenoids, and glutathione (Mittler 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been shown that gamma rays can interact directly with different cellular components by crossing multiple levels to reach membranes, proteins, and nucleic acids [ 64 ]. Several studies have reported an intensification of antioxidant enzymes activity in plants in response to various ionizing radiation treatments [ 18 , 38 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…These may include the use of the plant growth regulators—PGR [ 7 , 8 ], the phytohormones [ 9 , 10 ], or plant growth-promoting rhizobacteria—PGPR [ 11 , 12 ] in order to diminish or eliminate the negative effects of salinity and to obtain the plants that are able to manage salinity stress. In addition, numerous studies of gamma radiation and salinity effects, applied separately or simultaneously, on mono- or dicotyledonous species, such as: Oryza sativa [ 13 , 14 ], Medicago sativa [ 15 ], Ambrosia maritime [ 16 ], Vigna sinensis [ 17 ], Osmanthus fragrans [ 18 ], Moringa oleifera [ 19 ], have been performed. According to Macovei et al [ 13 ], gamma irradiation treatment can enhance the resistance of some plants to abiotic stress conditions, such as salt and drought, by intensification of antioxidant enzymes activity and activation of Transcription-Coupled Nucleotide Excision Repair (TC-NER) pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Geng et al [16] present a study on Osmanthus fragans (sweet olive), an ornamental plant, which has important commercial applications (e.g., for perfume production). They showed that moderate doses of γ-radiation of seeds have a long-lasting effect on the salt tolerance of seedlings that went along with a generally enhanced level of antioxidative enzyme activities and reduced superoxide accumulation.…”
Section: Salinity and Combined Stresses: From Soil Amendment To Redoxmentioning
confidence: 99%